Hubungan Literasi TBC dengan Stigma Tuberkulosis Masyarakat di Kelurahan Pekunden Semarang - Yusthin Meriantti Manglapy; Tiara Fani; Lice Sabata; Dani Miarso (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Community TB stigma is one of the obstacles to seeking TB treatment. Therefore it is necessary to know how the role of health literacy in TB disease against TB stigma.An observational study with a cross-sectional approach was conducted to measure the relationship between TB literacy and TB stigma. The number of respondents in this study was 102, who live in Pekunden Village and aged >= 18 years were taken incidentally. TB literacy and TB stigma were measured using interviews using a questionnaire.The results showed that 70.6% of respondents were female, most were 47 years old, 54% were unemployed, and 79.4% had heard of TB information before. As many as 48% of respondents are in the problematic and inadequate literacy category. As many as 48% of respondents gave a negative TB stigma. Spearman's rank test results with a 95% confidence level showed a relationship between TB literacy and tuberculosis stigma (p=0.0001; r=0.344)The prevention carried out becomes an action that is considered a stigma for the community. Follow-up is needed to see from the perspective of TB literacy and the behavior of TB patients.